First International Polar Year, 1882-83 - Taylor, C.J. (ARCTIC, 1981)
During 1882-83 eleven countries cooperated in a project to study the geophysics and geodesy of the polar regions by establishing 14 research stations. Three of these were located in Canada's Arctic: one each by the United States, Germany and Britain. They accumulated data on terrestial magnetism and boreal phenomena and brought back valuable information on arctic living.